Interview with Prof. Dr. Benjamin List: Nobel Laureate in Chemistry 2021. Issue 44 (12th July 2022) - Dilanas, Melina E. A.; Dobbelaar, Emiel; Gerischer, Charlotte M.; Haseloer, Alexander; John, Torsten; Neumeier, Claudia
Abstract: In an interview with Benjamin List, winner of the 2021 Nobel Prize in Chemistry, members of the Young Chemists' Network (JCF) of the German Chemical Society (GDCh) asked him about his science, his career, and the academic system. Benjamin List, Director at the Max‐Planck‐Institut für Kohlenforschung in Germany, was awarded the Nobel Prize together with David W. C. MacMillan (Princeton University, USA) for the development of asymmetric organocatalysis. After studying chemistry at the Free University of Berlin, he received his doctorate from Goethe University in Frankfurt. He discovered the amino acid proline to be an efficient catalyst and thus co‐founded the field of organocatalysis. In 2016, he received the Gottfried Wilhelm Leibniz Prize, which is considered the most important research award in Germany. Abstract : Early‐career chemists from the Young Chemists' Network (JCF) of the German Chemical Society (GDCh) interviewed Benjamin List, winner of the 2021 Nobel Prize in Chemistry. They spoke to him about his science, his career and the academic system. Benjamin List is a Director at the Max‐Planck‐Institut für Kohlenforschung in Germany. He received the Nobel Prize together with David W. C. MacMillan (Princeton University, USA) for the development of asymmetric organocatalysis. (Photo: Henning Kretschmer/Max‐Planck‐Institut für Kohlenforschung).